Harnessing Surface Wrinkling–Cracking Patterns for Tunable Optical Transmittance. Issue 19 (27th July 2017) - Li, Zhengwei; Zhai, Yao; Wang, Yu; Wendland, Griffith M.; Yin, Xiaobo; Xiao, Jianliang
Abstract : Optical devices with tunable specular optical transmittance have recently attracted great interest due to their wide range of applications. However, the reported methods of realizing tunable optical transmittance suffer from complex fabrication processes, high cost, unstable materials, or low tuning range. In this study, a simple, cheap, and highly effective approach to achieve large tuning range of optical transmittance through harnessing surface wrinkling–cracking patterns on polydimethylsiloxane (PDMS) films is reported. The surface wrinkling–cracking patterns are induced by stretching ultraviolet/ozone‐treated PDMS films and can effectively scatter the light transmitted through the films. With moderate 50% uniaxial tensile strain, the optical transmittance can be tuned between 92 and 9.2%. The films can be reversibly tuned between transparent and opaque for 1000 cycles without losing structural integrity and optical performance, with promising application in smart windows. By patterning the surface wrinkling–cracking patterns, an elastomeric switchable display is also demonstrated, which can be turned "ON" and "OFF" by mechanical strain. The material design demonstrated in this work offers a promising means to dynamically tune the optical properties of functional materials via strain‐controlled surface topography. This study can find applications in various optical devices and systems that require tunable optical properties. Abstract : Large optical transmittance modulation (83%) via surface wrinkling–cracking patterns on elastomeric polydimethylsiloxane films is reported. Such films can be reversibly tuned between transparent and opaque for 1000 cycles without losing structural integrity and optical performance. By patterning the surface wrinkling–cracking patterns, an elastomeric switchable display is also demonstrated, which can be turned "ON" and "OFF" by mechanical strain.